A multi‐tiered approach to safety education. (8th July 2013) - Oates, Kim; Sammut, John; Kennedy, Peter
Summary Background: The World Health Organization has recognised that patient safety education should begin at the undergraduate level. This should not just be for medical students, but for all students in the health professions. Although all students in the health professions should receive a basic grounding in patient safety, there is also a need to develop future leaders in this field. As a result of widespread early student exposure, some students may become interested in learning more. It follows that a postgraduate approach is also needed. Innovations: The New South Wales Clinical Excellence Commission (CEC) has initiated a tiered approach to patient safety education by providing patient safety teaching in medical, nursing and allied health schools. Teaching is provided in cooperation with the host university, and is interactive, using a mixture of interactive lectures, video clips, films and break‐out groups to discuss scenarios and feedback from students to their peers about the concepts they have discussed. For medical graduates, the CEC has initiated patient safety teaching in the early postgraduate years, and provides an elective in patient safety for trainee doctor specialists as part of their accredited training. This process helps to identify and mentor future medical leaders in this field. Implications: In addition to teaching the core principles of patient safety to a wide range of students in the health professions, an approach for developing future leaders will provide additional opportunities for motivated students and create opportunities for continuing development in the early postgraduate years and beyond.